Systematic Literature Review: Religious Ethics, Teacher Competence and Artificial Intelligence - Sayekti, Siskha Putri; Hajar, Munakhiroh El; Dahlan, Zaeni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This article presents a Systematic Literature Review (SLR) that synthesizes empirical studies on the integration of religious ethics, teacher competence, and Artificial Intelligence (AI)-enhanced deep learning within formal education. Guided by the PRISMA 2020 protocol, the review draws on searches conducted in Scopus, Web of Science, ERIC, IEEE Xplore, and Google Scholar. Inclusion criteria focused on empirical studies involving teachers or educators that examined AI use in relation to ethical or religious values, teacher competence, and 21st-century skills. From 1,204 initial records, 18 studies met the eligibility criteria and were analyzed descriptively and thematically. The findings reveal a shift in teacher competence from purely technical AI skills toward a holistic framework encompassing pedagogical, ethical, and human-centered dimensions, including awareness of AI dependency risks and their implications for 21st-century skills. Religious ethics, although still limited in their explicit integration, function primarily as a normative value framework that emphasizes moral responsibility, justice, and human dignity in the use of AI. This review highlights the need for an integrative model linking religious ethics, teacher competence, and AI-enhanced deep learning to inform educational policy, curriculum development, and teacher professional training. Such integration ensures that AI in education not only improves learning efficiency but also strengthens character formation and learners’ 21st-century skills. The article contributes by (1) providing a systematic and up-to-date mapping of empirical research at the intersection of ethics, teacher competence, and AI-based learning; (2) proposing an integrative conceptual model explaining how ethical values and teacher competence jointly mediate the pedagogical impact of AI; and (3) identifying future research directions emphasizing value-based, human-centered, and ethically responsible AI implementation in education.